2018
DOI: 10.1021/acs.energyfuels.8b00545
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Gas Transport Properties of Cross-Linked Poly(ethylene glycol diacrylate) (XLPEGDA) and XLPEGDA/TiO2 Membranes with a Focus on CO2 Separation

Abstract: Poly­(ethylene oxide) (PEO)-based membranes are known as outstanding candidates for carbon dioxide (CO2) separation as the major greenhouse gas responsible for global warming. In this paper, gas transport properties (solubility, permeability, and diffusivity) of neat and nanocomposite cross-linked poly­(ethylene glycol diacrylate) (XLPEGDA) membranes were investigated for CO2 as well as CH4, C2H4, C2H6, C3H8, H2, and N2 gases. XLPEGDA as a low-molecular-weight PEO, has not been studied much, compared to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…In this regard, several works have previously reported the adequacy of using the Flory–Huggins model to fit convex-shaped sorption isotherms of different solvent vapors, such as methanol, ethanol, or butanol, in membranes made of the family of Pebax copolymers or the sorption of water vapor through the Pebax 1074 grade . Besides, good correlations were found for the sorption of CO 2 in similar polymers to Pebax, such as crosslinked PEO or crosslinked PEO diacrylate membranes . However, to the best of our knowledge, this model has not been widely applied to describe gas solubility in CILPMs. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, several works have previously reported the adequacy of using the Flory–Huggins model to fit convex-shaped sorption isotherms of different solvent vapors, such as methanol, ethanol, or butanol, in membranes made of the family of Pebax copolymers or the sorption of water vapor through the Pebax 1074 grade . Besides, good correlations were found for the sorption of CO 2 in similar polymers to Pebax, such as crosslinked PEO or crosslinked PEO diacrylate membranes . However, to the best of our knowledge, this model has not been widely applied to describe gas solubility in CILPMs. …”
Section: Resultsmentioning
confidence: 99%
“…52 Besides, good correlations were found for the sorption of CO 2 in similar polymers to Pebax, such as crosslinked PEO 38 or crosslinked PEO diacrylate membranes. 53 However, to the best of our knowledge, this model has not been widely applied to describe gas solubility in CILPMs.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The introduction of CO 2 -affinitive functional groups can lead to the creation of 'reverse selective' membrane whereby the permeation of CO 2 (3.3 Å) is more favorable than that of smaller/lighter gases especially H 2 (2.9 Å) [244][245][246]. Compared to H 2 -selective membrane, reverse selective membrane is deemed more practical for separation of H 2 -CO 2 pair because CO 2 is directly removed from the system while purified H 2 which is still pressurized is retained and passed down the production line [36,247]. This could contribute to a substantial cost saving for the purification process as recompression of H 2 stream is omitted.…”
Section: Enhancing Gas Separation Performancementioning
confidence: 99%
“…The application of a membrane for gas separation is closely associated with the energy sector, in which the removal of contaminant gases such carbon dioxide (CO 2 ) and hydrogen sulfide (H 2 S) is critical for improving the calorific values of the gaseous feedstock to maximize power generation [33][34][35]. Since CO 2 and H 2 S are corrosive, the elimination of both gases can also prevent damage to system instruments and pipelines [36,37]. Contemporarily, CO 2 separation via a polymeric-based membrane is widely explored in applications such as natural gas sweetening [30,38,39], hydrogen purification [40,41] and biogas upgrading [31,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the well-known trade-off between permeability and selectivity values of polymeric membranes is a predominant challenge encountered for their industrial application. Therefore, development of advanced materials with high affinity for CO 2 can extend their capability for developing membrane technology for CO 2 removal. , Lin and Freeman , found that poly­(ethylene oxide) (PEO)-based membranes are promising candidates for CO 2 separation from light nonpolar gases such as N 2 , CH 4 , and H 2 , providing high CO 2 solubility selectivity. Indeed, the presence of the polar electron-rich ether oxygen (EO) units in these polymers backbones results in high affinity to CO 2 molecules due to dipole–quadrupole interactions. However, development of PEO-based membranes with high EO content is rather challenging owing to strong crystallization tendency, caused by their high chain packing, resulting in drastic CO 2 permeation decline . Moreover, PEO-based membranes mostly suffer from lack of mechanical strength …”
Section: Introductionmentioning
confidence: 99%